Nutritional aspects and larvae preference of Anticarsia gemmatalis Hüebner, 1818 (Lepidoptera: Noctuidae) on damaged and undamaged soybean cultivars - De Bortoli, Sergio Antonio; Murata, Afonso Takao; De Bortoli, Caroline Placidi; de Magalhães, Gustavo Oliveira; Dibelli, Wanderlei (Comunicata Scientiae, 2011)
Resistance to insects can be due to chemical factors present in the plant, and, according to the nature of the compounds, the resistance may be constitutive (independent of environmental stress), or induced by stress. In the case of soybeans, there are citations of constitutive and induced resistance, and for induced resistance, the value of information produced by the plant depends, for example, on the degree of the herbivore infestation. The induced resistance due to injury caused by the feeding of caterpillars Pseudoplusia includens in soybean occurs and has its peak near the 10th day after the injury. This way, the objective of this paper was to study the influence of previous injury in soybean genotypes, ‘Embrapa 4’ and ‘BR 37’, through the soybean defoliation by caterpillars, the preference and nutrition of Anticarsia gemmatalis. From the results obtained, it was possible to observe that the genotype ‘Embrapa 4’ is preferred by the caterpillars of A. gemmatalis in relation to ‘BR 37’, with a much higher leaf area consumed. As for the first one, an evident induction of resistance by a prior herbivory occurs, since the tests performed after defoliation show negative influence on insect development; consumption and use of food indexes were, in general, higher also for the variety ‘Embrapa 4’ which was not injured.